Juridical Implications of the Issuance of Covernotes by A Notary as Basis of Disbursing Credit of Banking - Vikriatuz Zahro; Iswi Hariyani; Iwan Rachmad Soetijono (Jurnal Ilmu Kenotariatan, 2023)
Notaries have the authority to make authentic deeds, apart from that notaries can also sometimes issue certificates or commonly known as covernotes. The legal consequences and limitations of liability for publishing a covernote in this case are examined. On what basis is the covernote used as the basis for credit disbursement? Because in this case it could have implications for the notary who will be involved in a legal case involving the covernote he published. The aim of writing this article is to find out, reveal and find out the notary's impression regarding the covernote he publishes. This writing uses a normative juridical approach, using primary and secondary legal sources. Primary legal materials are obtained from statutory regulations and secondary legal materials are obtained from library materials, archives and documents related to the research object. The results of the discussion show that the juridical application of covernotes is not a notarial legal product as regulated in the Law on the Position of Notaries, but is only a certificate issued at the request of the parties so that it does not give rise to rights and obligations for the parties. The covernote is a pure form of trust and moral bond from the creditor towards the notary as a public official who is neutral, independent and impartial in helping the public to support business relations transactions in the era of competitive economic development. Responsibility for the information in the covernote is the personal responsibility of the notary. KEYWORDS: Notary, Covernote, Legal Consequences.